Acceptance (qabul) and taking possession (qabd) of hibah under Islamic law and the decision of the Syariah Courts in Malaysia - Hj Ibrahim, Badruddin (International Islamic University Malaysia, 2009)
One of the important components in the creation of contract in Islamic law, apart from the contracting parties ('aqidan) and subject matter of contract (mahal al-'aqd), is formation (sighah). It consists of two essential elements i.e. offer (ijab) and acceptance (qabul). The absence of formation will render the contract invalid and imperfect. Nevertheless, in the case of hibah as it is a kind of contract of charity (tabarru'), the issue arises as to whether the element of acceptance is required in order to constitue a valid hibah. Added to this is the issue of whether hibah is completed and ownership of property transferred to the recipient as is the case with other types of contract when all of the above three components of contract and their requirements are fulfilled. This study examines issues relating to these two important matters of hibah, since disputes among parties in the Syariah Courts of Malaysia mostly involve these. The examination focuses on the positions of Muslim jurists of the four well-known schools of law, i.e. Shafi'i, Hanafi, Maliki and Hanbali, on the issues. In addition, as the law of hibah for Muslims in Malaysia is mostly uncodified, the study also examines the law that has been applied by various Syariah Courts in Malaysia regarding these issues, especially whether their decisions are solely based on the law according to the school of Shafi'i. This is in order to find out an acceptable set of rules that could govern the creation of a valid and perfect hibah.